Rethinking agricultural policy regimes food security, climate change and the future resilience of global agriculture - Almås, Reidar, 1943-; Campbell, Hugh, 1964- (Research in rural sociology and development, 2012)
For many decades debates about the future of developed world agriculture policy have been dominated by a long political conflict between European/multifunctional policy regimes and the global trend towards trade liberalisation. The stalemate that had emerged between these two positions by 2000 has now been dramatically reconfigured. This book argues that there are four reasons why this area of policy has now reopened to wider debate: The World Food Crisis of 2008-2011 has signalled a potential end to the era of cheap food. The emergence of climate change as a core policy concern has shifted key targets for agricultural policy. New trends towards 'neo-productivist' agricultural policy have emerged to challenge multifunctional approaches to agriculture. New academic ideas around resilience of food chains and relevant policy interventions have challenged established approaches to achieving agricultural sustainability. Through international case studies, this book evaluates how these new policy challenges are having an impact on specific agricultural policy regimes, and what future lessons might be learnt from key policy experiments around neoliberalism and multifunctionality.